The The Influence Of Leadership and Work Discipline On Employee Performance In The Ragional Office Of The Ministry Of Religion Of Gorontalo Province - Pateda, Rahmatia; Aneta, Asna; Abdussamad, Juriko (PROVIDER JURNAL ILMU PEMERINTAHAN, 2025)
This research aims to determine the impact of leadership and work discipline on employee performance at the regional office of the Gorontalo provincial ministry of trust. The research approach used in this research is quantitative, where the sample in this research is 35 employees using a research approach and research design. The data collection technique was carried out by distributing questionnaires or questionnaires to the data analysis technique used was multiple regression analysis. The results of the regression analysis test indicate the influence of leadership and work discipline on employee performance in the regional office of the Gorontalo provincial ministry of trust. Using this, the first hypothesis (H1) can be demonstrated or accepted. The R Square value is 0.412, in other words, 41.2% of the independent variables, namely (X1) Leadership, (X2) work discipline contribute to the variable (Y) employee performance, while the balance is 58.8% in the form of donations from other variables not examined in this research. The results of the regression analysis test show the influence of leadership and work discipline on employee performance in the Regional Office of the Ministry of Religion, Gorontalo Province. Thus the first hypothesis (H1) can be proven or accepted. The R Square value is 0.412, in other words, 41.2% of the independent variables, namely (X1) Leadership, (X2) Work Discipline contribute to the variable (Y) Employee Performance, while the remaining 58.8% is in the form of contributions from other variables not examined in this research. Penelitian ini bertujuan buat mengetahui imbas kepemimpinan dan disiplin Kerja Terhadap Kinerja Pegawai pada kantor daerah kementerian kepercayaan provinsi Gorontalo. Pendekatan penelitian yang digunakan pada penelitian ini yaitu kuantitatif, dimana sampel pada penelitian ini berjumlah 35 orang pegawai dengan memakai pendekatan penelitian serta desain penelitian. Teknik pengumpulan data dilakukan dengan cara menyebarkan angket atau kuesioner kepada teknik analisis data yang digunakan adalah analisis regresi berganda. Hasil uji analisis regresi yang menandakan pengaruh kepemimpinan serta Disiplin Kerja Terhadap Kinerja pegawai di kantor daerah kementerian kepercayaan provinsi Gorontalo. Menggunakan demikian hipotesis pertama (H1) dapat ditunjukan atau diterima. Nilai R Square sebesar 0,412 dengan kata lain itu sebanyak 41,2% dari variable bebas yaitu (X1) Kepemimpinan, (X2) disiplin kerja memberikan donasi buat variable (Y) kinerja pegawai, adapun keseimbangan sebanyak 58,8% berupa donasi dari variabel lain yang tidak diteliti pada penelitian ini. Hasil uji analisis regresi yang menunjukan Pengaruh Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Pegawai Di Kantor Wilayah Kementerian Agama Provinsi Gorontalo. Dengan demikian hipotesis pertama (H1) dapat dibuktikan atau diterima. Nilai R Square sebesar 0,412 dengan kata lain bahwa sebesar 41,2% dari variable bebas yaitu (X1) Kepemimpinan, (X2) Disiplin Kerja memberikan kontribusi untuk variable (Y) Kinerja Pegawai, adapun sisanya sebesar 58,8% berupa kontribusi dari variable lain yang tidak diteliti dalam penelitian ini.